Phytochemical profile, antioxidant potential, and antibacterial activity of Thai polyherbal formulation, a Ya Kae Rok Bit remedy - CHAWALIT YONGRAM; PALAPON CHIMPALEE; SUWADEE CHOKCHAISIRI; SASIPEN KRUTCHANGTHONG; JIRAPORN SONGSRI; THAVATCHAI KAMOLTHAM; PANUPAN SRIPAN (Society for Indonesian Biodiversity, 2026)
Abstract. Yongram C, Chimpalee P, Chokchaisiri S, Krutchangthong S, Songsri J, Kamoltham T, Sripan P. 2026. Phytochemical profile, antioxidant potential, and antibacterial activity of Thai polyherbal formulation, a Ya Kae Rok Bit remedy. Biodiversitas 27 (5): d270516. https://doi.org/10.13057/biodiv/d270516. This study investigated the quantitative and qualitative phytochemical diversity and biological activities of Ya Kae Rok Bit (YKRB) extracts prepared using different solvents (hexane, ethyl acetate, and ethanol). Total phenolic, flavonoid, and tannin contents were also evaluated. Antioxidant capacity was evaluated using DPPH, ABTS, and FRAP assays, while antibacterial activity against Escherichia coli ATCC 25922 and Staphylococcus aureus ATCC 25923 was determined by disc diffusion and broth microdilution. GC-MS analysis identified 28 phytochemical constituents, including neutral cannabinoids, with tetrahydrocannabinol (23.24-27.91%) and cannabinol (14.18-21.06%) as relatively abundant compounds based on peak area normalization, together with macelignan (6.34-10.55%). HPLC confirmed the highest Δ9-THC content in the hexane extract (6.92 mg/g extract). The extracts showed measurable antioxidant activity in the DPPH assay (IC50 = 56.72-95.25 µg/mL) and stronger radical scavenging activity in the ABTS assay (IC50 = 23.26-26.93 µg/mL), with reducing capacity observed in the FRAP assay (200.92 mmol Fe²⁺/100 g extract). Moreover, YKRB showed antibacterial activity against S. aureus (MIC = 25 mg/mL), while no activity was observed against E. coli. These findings demonstrate solvent-dependent phytochemical variation and provide preliminary evidence of antioxidant and selective antibacterial activities of YKRB extracts.